Archaeology : what it is, where it is, and how to do it - Wilkinson, Paul, 1946- (Archaeopress Archaeology, 2020)
A practical introduction covering all core aspects of archaeology, this book is perfect for anyone looking to get involved in archaeology on a professional level or as a volunteer, or simply wanting an overview of the discipline. Aerial and ground survey, excavation and fieldwork, recording methods, soil sampling and small finds are all discussed.